Radical Christianity in Palestine and Israel liberation and theology in the Middle East - Kuruvilla, Samuel J. (Library of modern religion, 2013)
"Christianity arose from the lands of biblical Palestine and, regardless of its twentieth century association with the Arab-Israeli conflict, to Christians around the world it remains first and foremost the birthplace of Christianity. Nevertheless the size of the Christian population among Palestinians today living in Israel and the Palestinian territories is now relatively insignificant. Here Samuel J. Kuruvilla argues that Christian Palestinians often employ politically astute as well as theologically radical means in their efforts to appear relevant as a minority community within Israeli and Palestinian societies. He charts the development of a theology of Christian liberation, particularly in the work of Palestinian Anglican cleric Naim Stifan Ateek and Palestinian Lutheran Pastor Mitri Raheb, among others, as part of the Palestinian people's struggle for independence. In doing so, Kuruvilla provides a new perspective of the Israel-Palestine conflict and the role of Christians within it." -- from the publisher's website.